1990
DOI: 10.1002/food.19900340114
|View full text |Cite
|
Sign up to set email alerts
|

Role of zinc in regulating the testicular function Part 3. Histopathological changes induced by dietary zinc deficiency in testes of male albino rats

Abstract: Zinc deficiency affects the testicular tissues adversely. The testes of zinc-deficient rats showed variable degrees of degeneration compared to both control and zinc-supplemented ones. Initially, there was an early pronounced spermatic arrest followed by a series of degeneration of the cellular layers constituting the seminiferous tubules in the zinc-deficient rats. Degenerative changes were additionally demonstrated in the interstitial tissue cells of the zinc-deficient rats. These histopathological observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It is known that dietary zinc deficiency in particular leads to hypogonadism [15]. However, it is observed that previous studies have mainly focused on the relation between the male reproductive system and zinc [1,14,15]. It was shown in a study by Om and Chun [16] that zinc deficiency caused an inhibition on LH and estrogen levels.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is known that dietary zinc deficiency in particular leads to hypogonadism [15]. However, it is observed that previous studies have mainly focused on the relation between the male reproductive system and zinc [1,14,15]. It was shown in a study by Om and Chun [16] that zinc deficiency caused an inhibition on LH and estrogen levels.…”
Section: Discussionmentioning
confidence: 94%
“…Zinc has a key role in the physiology of the reproductive system [14]. It is known that dietary zinc deficiency in particular leads to hypogonadism [15].…”
Section: Discussionmentioning
confidence: 99%
“…The trace element zinc is speculated to play a critical role in sexual development. Zinc deficiency was found to disrupt testicular tissue [ 40 ], impair spermatogenesis [ 41 ], and reduce testosterone levels [ 42 ], while zinc supplementation improved the sexual behavior of adult male rats in a dose-dependent manner by enhancing testosterone secretion [ 43 ]. Moreover, Prasad et al [ 44 ] reported a positive correlation between cellular zinc concentration and serum testosterone level in healthy men.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] Dietary Zn deficiency for 4 weeks in the albino rat has been reported to arrest the spermatogenesis process and seminiferous tubule degeneration. [ 42 ] ZDD fed male Balady rabbits for 120 days were reported to have decreasede secretory functions in epididymis as compared with control. [ 43 ] Prostate histopathology showed folded lobules and lobular damage in BPA, ZDD, and BPA + ZDD exposed animals as compared with control.…”
Section: Discussionmentioning
confidence: 99%